2019
DOI: 10.1152/ajpendo.00065.2019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic inferences on metabolic dysfunction in posttraumatic stress disorder from an integrated model and multiomic analysis: role of glucocorticoid receptor sensitivity

Abstract: Posttraumatic stress disorder (PTSD) is associated with neuroendocrine alterations and metabolic abnormalities; however, how metabolism is affected by neuroendocrine disturbances is unclear. The data from combat-exposed veterans with PTSD show increased glycolysis to lactate flux, reduced TCA cycle flux, impaired amino acid and lipid metabolism, insulin resistance, inflammation, and hypersensitive hypothalamic-pituitary-adrenal (HPA) axis. To analyze whether the co-occurrence of multiple metabolic abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 90 publications
(98 reference statements)
0
25
0
6
Order By: Relevance
“…(vi) The influences of other causes of perturbation and response of the HPA axis (e.g., stress and posture) should be added to the model. (vii) The mathematical model presented in this work can be expanded to explicitly account for the influence of cortisol on the dynamics of metabolic mediators such as glucose and insulin as has been shown by others [ 57 , 60 , 61 , 62 , 63 ]. Such extensions would enable further investigation of the interplay among timing of meals, sleep cycles, and light exposure, which are often perturbed together for extended periods in chronic shift workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(vi) The influences of other causes of perturbation and response of the HPA axis (e.g., stress and posture) should be added to the model. (vii) The mathematical model presented in this work can be expanded to explicitly account for the influence of cortisol on the dynamics of metabolic mediators such as glucose and insulin as has been shown by others [ 57 , 60 , 61 , 62 , 63 ]. Such extensions would enable further investigation of the interplay among timing of meals, sleep cycles, and light exposure, which are often perturbed together for extended periods in chronic shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that cortisol exhibits prominent pulsatile ultradian rhythms, which are not captured by the dynamics of our model. Nevertheless, previously published models of the HPA axis based on a similar framework that have primarily studied the circadian dynamics of this system have yielded insightful physiologically findings in understanding the mechanisms contributing to disruption in cortisol circadian rhythms in PTSD and depression [ 60 , 63 , 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…A few other research studies reported that rats exposed to imminent shock have elevated p11 levels in prefrontal cortex. This study also reported that the synthetic glucocorticoid dexamethasone enhanced p11 expression through glucocorticoid response elements (GREs) in the p11 promoter, which has implications in psychopathology during PTSD [ 66 ]. Thus, the p11 protein plays a significant role in mood regulation during PTSD, and it is essential to develop novel therapeutic modalities to modulate the function of p11 in PTSD patients comorbid with major depressive disorder [ 65 ].…”
Section: Neurotransmitter Genomics and Ptsdmentioning
confidence: 99%
“…For example, macrophages accumulate inside adipose tissue during obesity/insulin resistance generating cytokines and adipokines that may lead to inflammation [ 72 ]. Hyperinsulinemia sensitizes adipose tissue to lipid synthesis, which is associated with increased activity of glucocorticoids [ 66 ].…”
Section: Metabolic Changes and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation